الآليات القانونية لمكافحة التمييز العنصري وخطاب الكراهية في الجزائر - سامية نافع; نوال شعابنية (My University, 2026)
Summary In the memorandum, we addressed the topic of: the legal mechanisms for combating racial discrimination and hate speech in Algerian law, considering them as crimes that threaten human rights and undermine the principles of equality and peaceful coexistence within society. The definition of the crimes of racial discrimination and hate speech was discussed, and the forms of each were explained. Discrimination is based on differentiating between individuals because of race, religion, or origin, while hate speech is represented by any statement, action, or publication that incites hatred, violence, or exclusion. The study also addressed the preventive mechanisms adopted to reduce the spread of these crimes by promoting a culture of tolerance and respect for human rights through educational and media institutions, and the role of civil society. It further emphasized raising awareness of the dangers of the misuse of social media in disseminating extremist and hate-inciting ideologies. The report also touched upon international efforts to combat these crimes through international agreements and conventions that criminalize all forms of discrimination and incitement to hatred. At the national level, the study focused on the provisions of Law 20-05 concerning the prevention and combating of racial discrimination and hate speech. This law is considered one of the most important legal texts addressing these two crimes, criminalizing various related acts and specifying the prescribed penalties, judicial mechanisms, and preventive and deterrent measures aimed at protecting society, maintaining security and stability, and consolidating the values ​​of equality and coexistence among members of Algerian society. .......................... ملخص تناولنا في المذكرة موضوع :الآليات القانونية لمكافحة التمييز العنصري وخطاب الكراهية في القانون الجزائري باعتبارهما من الجرائم التي تهدد حقوق الإنسان، وتمس بمبادئ المساواة والتعايش السلمي داخل المجتمع، وقد تم التطرق إلى تعريف جريمتي التمييز العنصري وخطاب الكراهية ،وبيان أشكال كل منهما ،حيث يقوم التمييز على التفرقة بين الأفراد بسبب العرق، أو الدين، أو الأصل، بينما يتمثل خطاب الكراهية في كل قول، أو فعل، أو منشور من شأنه التحريض على الكراهية ،أو العنف، أو الإقصاء. كما تناولنا في الدراسة الآليات الوقائية المعتمدة للحدّ من انتشار هذه الجرائم من خلال نشر ثقافة التسامح ،واحترام حقوق الإنسان عبر مؤسسات التربية والإعلام، ودور المجتمع المدني، اضافة إلى تعزيز الوعي بخطورة الاستعمال السيئ لوسائل التواصل الاجتماعي في نشر الأفكار المتطرفة والمحرضة على الكراهية .وتطرقنا في المذكرة أيضا إلى الجهود الدولية المبذولة لمكافحة هذه الجرائم من خلال الاتفاقيات والمواثيق الدولية التي أكدت على تجريم جميع أشكال التمييز والتحريض على الكراهية ،أما على المستوى الوطني فقد كرست الدراسة على أحكام القانون 20-05 المتعلق بالوقاية من التمييز العنصري وخطاب الكراهية ومكافحتهما، والذي يعد من أهم النصوص القانونية لهاتين الجريمتين وجرم مختلف الأفعال المرتبطة بهما، كما حدد العقوبات المقررة والآليات القضائية والتدابير الوقائية والردعية التي تهدف إلى حماية المجتمع والحفاظ على الأمن والاستقرار، وترسيخ قيم المساواة والتعايش بين أفراد المجتمع الجزائري . .......................... Résumé Ce mémorandum aborde la question des mécanismes juridiques de lutte contre la discrimination raciale et les discours de haine en droit algérien, considérés comme des infractions qui menacent les droits humains et portent atteinte aux principes d'égalité et de coexistence pacifique au sein de la société. La définition de ces infractions et leurs différentes formes sont examinées. La discrimination repose sur la distinction entre individus en raison de leur race, de leur religion ou de leur origine, tandis que les discours de haine se caractérisent par toute déclaration, action ou publication incitant à la haine, à la violence ou à l'exclusion. L'étude examine également les mécanismes de prévention mis en œuvre pour limiter la propagation de ces infractions, notamment la promotion d'une culture de tolérance et de respect des droits humains par le biais des institutions éducatives et médiatiques, ainsi que le rôle de la société civile. Elle souligne en outre la nécessité de sensibiliser le public aux dangers liés à l'utilisation abusive des réseaux sociaux pour diffuser des idéologies extrémistes et incitant à la haine. Le rapport aborde également les efforts internationaux déployés pour lutter contre ces infractions à travers les accords et conventions internationaux qui criminalisent toutes les formes de discrimination et d'incitation à la haine. Au niveau national, l'étude s'est concentrée sur les dispositions de la loi 20-05 relative à la prévention et à la lutte contre la discrimination raciale et les discours de haine. Cette loi est considérée comme l'un des textes juridiques les plus importants traitant de ces deux infractions. Elle érige en infraction divers actes connexes et précise les peines prévues, les mécanismes judiciaires et les mesures préventives et dissuasives visant à protéger la société, à maintenir la sécurité et la stabilité, et à consolider les valeurs d'égalité et de coexistence au sein de la société algérienne.
Keywords: Keywords: Racial discrimination crime – Hate speech crime – Preventive mechanisms – National Observatory – Repression; الكلمات المفتاحية: جريمة التمييز العنصري – جريمة خطاب الكراهية – الآليات الوقائية – المرصد الوطني – القمع; Mots-clés : Infraction de discrimination raciale – Infraction de discours de haine – Mécanismes de prévention – Observatoire national – Répression